DEVELOPMENT OF E-GOVERNMENT-BASED PUBLIC SERVICES IN THE CONTEXT OF REALIZING GOOD GOVERNANCE REGIONAL GOVERNMENT - Moh. Taufik; Khoerul Umam (Adisam Publisher, 2024)
The development of information and communication technology has offered solutions to improve the performance of public services that are more based on good governance. Readiness of human resources, regulations, budget, facilities and infrastructure are absolute things that must be provided in implementing e- government towards Good Governance. The aim of this studyTo describe Indonesian legal regulations in E-Government Development. To find out the obstacles to E-Government development. The type of research used in this research is field research with a qualitative research approach. This research uses the regional government of Brebes Regency, especially the management of public services, as the research object, with primary and secondary data sources, namely sources from regional government employees and regional regulations implemented in Brebes Regency. The results of this research show that the implementation of good governance in services to the community as one of the efforts in providing effective, efficient, transparent and accountable government in line with the implementation of the bureaucratic reform program in order to improve the quality of government administration requires the support of an electronic-based government system is in Brebes Regency.